Kritische Bemerkungen zu den Punica des Silius Italicus - Gärtner, Thomas (Exemplaria Classica, 2009)
The present paper discusses several questions of textual criticism concerning Sily´s epic "Punica", starting from Josef Delz’s Teubneriana edition.